The effects of two different doses of ultraviolet-A light exposure on nitric oxide metabolites and cardiorespiratory outcomes - Chris Monaghan; Luke C. McIlvenna; Luke Liddle; Mia Burleigh; Richard B. Weller; Bernadette O. Fernandez; Martin Feelisch; David J. Muggeridge; Chris Easton (European Journal of Applied Physiology, 2018)
Purpose The present study investigated different doses of ultraviolet-A (UV-A) light on plasma nitric oxide metabolites and cardiorespiratory variables. Methods Ten healthy male participants completed three experimental conditions, 7 days apart. Participants were exposed to no light (CON); 10 J cm 2 (15 min) of UV-A light (UVA10) and 20 J cm 2 (30 min) of UV-A light (UVA20) in a randomized order. Plasma nitrite [NO 2 − ] and nitrate [NO 3 − ] concentrations, blood pressure (BP), and heart rate (HR) were recorded before, immediately after exposure and 30 min post-exposure. Whole body oxygen utilization ( $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 ), resting metabolic rate (RMR) and skin temperature were recorded continuously. Results None of the measured parameters changed significantly during CON (all P > 0.05). $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR were significantly reduced immediately after UVA10 ( P < 0.05) despite no change in plasma [NO 2 − ] ( P > 0.05). Immediately after exposure to UVA20, plasma [NO 2 − ] was higher ( P = 0.014) and $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR tended to be lower compared to baseline ( P = 0.06). There were no differences in [NO 2 − ] or $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 at the 30 min time point in any condition. UV-A exposure did not alter systolic BP, diastolic BP or MAP (all P > 0.05). UV-A light did not alter plasma [NO 3 − ] at any time point (all P > 0.05). Conclusions This study demonstrates that a UV-A dose of 20 J cm 2 is necessary to increase plasma [NO 2 − ] although a smaller dose is capable of reducing $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR at rest. Exposure to UV-A did not significantly reduce BP in this cohort of healthy adults. These data suggest that exposure to sunlight has a meaningful acute impact on metabolic function.